Scollay Square and Court Street, ca. 1890 - Unknown (Tufts Archival Research Center, 2005)
Elevated view northwest of Scollay Square and Court Street. A statue of John Winthrop, located in the center of Scollay Square, is included near the lower-right corner of the photograph. Signage and awnings adorn the facades of (right to left) 73-97 Court Street, which line the northeast side of the street and are included in the right-half of the photograph. Signage and awnings adorn 1-28 Tremont Row, which are included along the left side of the photograph. Horse-drawn wagons, carriages and street railroads fill Court Street and Scollay Square. Pedestrians are also included in the photograph. 7 1/2 x 9 1/4, 7 5/8 x 9 1/2 overall Albumen prints